Технология изготовления автоэмиссионных кремниевых катодов субмикронных размеров - Druzhynin, A. A.; Holota, V. I.; Kogut, I. T. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
Modern fabrication technologies of field emission cathodes are analyzed. A practical method for forming topological elements of submicron dimensions is proposed. A CMOS-based technology using micron-scale photomasks has been developed and modeled for the fabrication of single-tip, multi-tip, and blade-type field emission silicon cathodes of submicron size. The results of electric field modeling for the field emission cathodes are presented.